A full 3D rigid block model for the collapse behaviour of masonry walls - Baraldi, Daniele; Cecchi, Antonella (European journal of mechanics, A, Solids, 2017)
This paper presents and validates a non-commercial rigid block model code for performing pushover analysis of one leaf masonry assemblages with regular texture, in three dimensional field. Hypotheses of rigid blocks and joints modelled as interfaces are adopted for representing historic masonry behaviour, characterized by dry joints or weak mortar joints having negligible size with respect to block size. Masonry elastic and inelastic behaviour is concentrated at joints by defining their normal, shear, bending and torsion stiffness and strength, adopting a Mohr-Coulomb criterion for restraining interface actions. The proposed model is an extension to the field of material nonlinearity of an existing code, moreover nonlinear analyses follow an effective approach introduced by authors for the in-plane case, based on the determination and update of the stiffness matrix of the masonry assemblage during the incremental analysis, accounting for damage. A numerical experimentation is performed for determining limit load multipliers and collapse mechanisms of several masonry walls subject to in-plane actions generated by self-weight and out-of-plane actions that may cause tilting or toppling of masonry assemblage portions. Dry and mortar joints are considered and existing case studies are adopted for calibrating the proposed model and evaluating its effectiveness. •A simple and effective model for 3D analysis of regular masonry is presented.•Model based on rigid blocks and elastic-plastic Mohr-Coulomb joints.•Pushover analyses with 3D rigid block model are performed.•Pushover curves, collapse loads and mechanisms are obtained for masonry specimens.•Numerical results are close to existing ones for panels with dry and mortar joints.